1976
DOI: 10.2307/1589278
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Monensin against Turkey Coccidiosis in Laboratory and Floor-Pen Experiments

Abstract: Monensin at 60, 80, or 100 ppm in feed reduced mortality and lesion scores while protecting against weight loss of turkeys infected with the major pathogenic species: Eimeria adenoides, E. meleagrimitis, and E. gallopavonis. With single and mixed infections in battery-cage experiments, the death rate of unmedicated turkey poults was 33-75%. Weight gains were significantly (P is less than or equal to 0.05) better with 100 ppm monensin than 60 ppm, as were also lesion scores. Under floor-pen conditions there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 7 publications
1
7
0
2
Order By: Relevance
“…DISCUSSION The results of this trial confirm that monensin may provide protection against coccidiosis for young poults reared on the floor. Similar conclusions have been reached by Anderson et al (1976) andMcDougald (1976). These results also suggest that the drug may be safely withdrawn at 10 weeks without mortality or reduction in weight gain due to coccidiosis ensuing.…”
Section: E Gallopavonis) Than the Upper Intestine (E Meleagrimitis)supporting
confidence: 80%
See 1 more Smart Citation
“…DISCUSSION The results of this trial confirm that monensin may provide protection against coccidiosis for young poults reared on the floor. Similar conclusions have been reached by Anderson et al (1976) andMcDougald (1976). These results also suggest that the drug may be safely withdrawn at 10 weeks without mortality or reduction in weight gain due to coccidiosis ensuing.…”
Section: E Gallopavonis) Than the Upper Intestine (E Meleagrimitis)supporting
confidence: 80%
“…Monensin shows promise in the control of turkey coccidiosis (Anderson et al, 1976;McDougald, 1976) but effects of withdrawal are unknown. Monensin alters oocyst production and may affect immunity development (Karlsson and Reid, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also reported the efficacy of this drug against Eimeria species in turkeys (Anderson et al, 1976;Long & Millard, 1977McDougald & McQuistion, 1978;Cabel et al, 1991;Schildknecht et al, 1995). In the USA, MON is approved for use in turkeys within the range of 60-99 ppm.…”
Section: Discussionmentioning
confidence: 88%
“…Monensin (Anderson et al, 1976;McDougald, 1976) was introduced in the 1970s, and for many years has been the most widely used ionophore for the control of coccidiosis in turkeys. Other ionophores effective against Eimeria in the turkey are lasalocid (Mitrovic et al, 1979), and maduramicin (Wang et al, 1989).…”
Section: Chemotherapymentioning
confidence: 99%